The timing of final closure along the Changchun-Yanji suture zone: Constraints from detrital zircon U-Pb dating of the Triassic Dajianggang Formation, NE China - Wang, B.; Zhou, J.; Wilde, Simon; Zhang, X.; Ren, S. (2015)
© 2015 Elsevier B.V. The Dajianggang Formation is located in the Changchun-Yanji suture zone of central Jilin Province and unconformably overlies the Changchun-Yanji Accretionary Complex (CYAC), which is a mélange resulting from subduction of the Jiamusi-Khanka Block (JKB) beneath the North China Craton (NCC). LA-MC-ICP-MS U-Pb dating of detrital zircon from four samples of the formation yields ages of 2516 to 216. Ma. Zircons with U-Pb ages at 2516-2501. Ma and 1897-1832. Ma indicate a provenance from Precambrian basement rocks of the NCC. The 525-482. Ma ages indicate a provenance from metamorphic rocks of Late Pan-African age in the JKB that have a tectonic affinity to the Central Asian Orogenic Belt (CAOB). Zircon grains with ages of 383-314. Ma and 275-250. Ma were likely derived from the underlying CYAC. The youngest population has a peak age of ca. 225. Ma, which together with Late Triassic fossils, suggests that deposition of the Dajianggang Formation was Late Triassic or younger. This result supports the view that the final collision of the JKB and NCC along the Changchun-Yanji suture took place before the Late Triassic. Furthermore, this closure time is at least 10-20. Ma later than closure along the Solonker-Xar Moron-Changchun suture in the Late Permian. We thus establish that the Changchun-Yanji suture is not related to the collision between the Siberia Craton (SC) and the NCC but was instead related to the Paleo-Pacific plate subduction. Consequently, the Changchun-Yanji suture is not the eastward extension of the Solonker-Xar Moron-Changchun suture as previously considered, but the southern margin of the Jilin-Heilongjiang high-pressure metamorphic belt (Ji-Hei HP belt), and resulted from westward subduction of the Paleo-Pacific Ocean. Thus, the Late Triassic marked the switch in subduction from the Paleo-Asian Ocean to the Paleo-Pacific Ocean in NE China.